2007
DOI: 10.4049/jimmunol.178.6.3702
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Defense against Pneumocystis carinii Mediated by a Novel Dectin-1 Receptor Fc Fusion Protein

Abstract: Pneumocystis carinii (PC) pneumonia is a leading opportunistic infection found among HIV-infected individuals worldwide. Although CD4+ T cell deficiency clearly correlates with susceptibility to PC pneumonia, murine models of disease indicate that PC-directed Abs may prevent infection and/or inhibit growth of existing PC within the lungs. Recognition of PC by alveolar macrophages involves the β-glucan receptor Dectin-1 and macrophage effector function against PC is enhanced by Abs derived from PC-vaccinated ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…Exploiting antibody responses that depend on Fc-FcγR interactions may help overcome some of the difficulties associated with vaccine development by widening the breadth and increasing the potency of the antibody response. Although the importance of generating optimal Fab-antigen interactions cannot be overestimated, improving Fc-FcγR interactions through adjuvants, by directly altering the Fc segment of mAbs or by other strategies provides another option for improving HIV vaccines and immunotherapies [4749]. …”
Section: Discussionmentioning
confidence: 99%
“…Exploiting antibody responses that depend on Fc-FcγR interactions may help overcome some of the difficulties associated with vaccine development by widening the breadth and increasing the potency of the antibody response. Although the importance of generating optimal Fab-antigen interactions cannot be overestimated, improving Fc-FcγR interactions through adjuvants, by directly altering the Fc segment of mAbs or by other strategies provides another option for improving HIV vaccines and immunotherapies [4749]. …”
Section: Discussionmentioning
confidence: 99%
“…Combining the extracellular domain of dectin-1 with the Fc portion of murine IgG1 in a fusion protein, Rapaka et al . were able to demonstrate enhanced uptake of Pneumocystis by AM and diminished severity of disease in a PCP model in severe combined immunodeficiency (SCID) mice [82]. …”
Section: Innate Immunitymentioning
confidence: 99%
“…We suspect that the specificities targeting ␤-glucan may play a role in fungal organism opsonization, immune-complex Fc receptor signaling, or potentially impairing fungal cell wall remodeling through direct binding to ␤-glucan. We have previously demonstrated that introduction of a Dectin-1-IgG1 Fc fusion protein diminished neutrophil recruitment to the lung in the setting of a developing infection and further that this molecule could significantly decrease the growth of Pneumocystis in the lungs of SCID mice but was insufficient in preventing infection (17). Although ␤-glucan is thought to predominate in the cyst form, in contrast to the more abundant trophic form, Dectin-1-IgG1 Fc was sufficient to significantly decrease the Pneumocystis pulmonary burden in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that natural IgM antibodies generated in the absence of exogenous stimuli, containing high quantities of specificities targeting ␤-glucan and chitosan/chitin, are able to impair the growth of Pneumocystis in the lungs during early stages of infection and impact properties of Th and B cell adaptive immune response differentiation (13). In addition, immunoadhesins with the ability to recognize ␤-glucan and bind murine Fc␥ receptors have also been shown to increase alveolar macrophagedependent killing of Pneumocystis (17) and complement-dependent killing of Pneumocystis (18) in murine models of infection. Here, we demonstrate that antibodies crossreactive with ␤-glucan and chitosan/chitin are products of adaptive antibody responses against Pneumocystis, and we dissect the requirements for CD4 ϩ T cells in isotype class-switching and mucosal antibody production against fungal cell wall carbohydrate antigens.…”
mentioning
confidence: 99%